2000
DOI: 10.1149/1.1393387
|View full text |Cite
|
Sign up to set email alerts
|

Planarization Processes and Applications III. As-Deposited and Annealed Film Properties

Abstract: In Parts I 1 and II 2 of this paper, it has been shown that both undoped and boron/phosphorus-doped germanosilicate thin films can be planarized over structures at significantly lower temperatures than other glasses, such as borophosphosilicate glass. However, variations in several film properties based on composition, such as water solubility, electrical leakage, and mechanical stress, must also be addressed. For instance, it is well known that germanium dioxide and germanosilicates rich in germanium oxide ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…We mostly relate these observations to an increase in the film electrical conductivity as the Ge concentration increased, which has been previously confirmed. [7] On the other hand, the built-in field of the 33-sccm sample is higher than that of the 0-sccm sample (pure SiOi), although the latter has a lower electrical conductivity. This points out that there should be an optimum electrical conductivity range for a given set of poling conditions.…”
Section: Thermal Poling Resultsmentioning
confidence: 96%
“…We mostly relate these observations to an increase in the film electrical conductivity as the Ge concentration increased, which has been previously confirmed. [7] On the other hand, the built-in field of the 33-sccm sample is higher than that of the 0-sccm sample (pure SiOi), although the latter has a lower electrical conductivity. This points out that there should be an optimum electrical conductivity range for a given set of poling conditions.…”
Section: Thermal Poling Resultsmentioning
confidence: 96%
“…In theoretical work [22], it was shown that quenching at high temperatures resulted in low-density silica. Local heating due to thermal spikes, produced upon impact, results in local surface diffusion and causes the tensile stress (therefore decrease of compressive stress) to rise as the micro-voids collapse [6]. Furthermore, ion and energetic neutral bombardment increases the surface mobility of chemically active species and increases the active sites on the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…The net stress in a material system consists of two components: the intrinsic stress (incorporated into the film during deposition, pertaining to composition, microstructure and particle bombardment [5]) and the extrinsic stress generated during cooling from the deposition temperature (∼300˚C) to room temperature due to the differences in thermal expansion coefficients between the film and substrate. It is known that the amount of stress in a film can be varied through addition of dopants [6]. The extrinsic stress level in a material system is set by using different dopants and varying their concentrations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We mostly relate these observations to an increase in the film electrical conductivity as the Ge concentration in the film is increased, which has been previously confirmed. [26] On the other hand, the built-in field of the 33-sccm sample is higher than that of the 0-sccm sample (pure SiO 2 ), although the latter has a lower electrical conductivity. This points out that there exists an optimum electrical conductivity range for a given set of poling conditions.…”
Section: Thermal Poling and Characterization Of The Poled Filmsmentioning
confidence: 96%